Variation in the Lipid Profile of Pacific Oyster ( Crassostrea gigas ) Cultured in Khanh Hoa Coast, Vietnam, Based on Location and Harvest Period - Minh Van Nguyen; Derrick Kakooza; Anh Phuong Thi Tran; Vy Thao Thi Tran (Polish Journal of Food and Nutrition Sciences)
The lipid profiles of the oyster Crassostrea gigas cultured in Khanh Hoa coast at three locations and harvested in different months throughout the year were compared. Seasonal and locational changes in total lipid (TL) content, phospholipid content, free fatty acid content, fatty acid (FA) composition, and thrombogenicity index were found. The total lipid content and n -3/ n -6 ratio in oysters from Ninh Hoa were higher compared to those from Cam Lam and Van Ninh. For oyster from all three farming areas, the total lipid content was the lowest during the two spawning seasons (May and September). Lipids from C. gigas were separated into neutral and polar lipid fractions using silica gel column chromatography. The amount of neutral lipids recovered from the oyster muscle was significantly higher than that of the polar lipids. The FA composition showed that C. gigas was abundant in saturated fatty acids (30.89–39.16 g/100 g TL), followed by polyunsaturated fatty acids (28.13–35.88 g/100 g TL), and monounsaturated fatty acids (19.32–23.75 g/100 g TL). The dominant polyunsaturated fatty acids of oysters from the three farming areas were eicosapentaenoic acid (9.09–13.77 g/100 g TL) and docosahexaenoic acid (6.71–16.47 g/100 g TL). Based on the present findings, it can be concluded that the Pacific oyster C. gigas cultured in Khanh Hoa, Vietnam is a promising source of highly nutritious exploitable lipids.